Dynamics of the RRNN interval of the cardiointervalogram depending on the specialization of the training process, stage of the annual preparation cycle and other factors (review) - D. A. Kataev; V. I. Tsirkin; V. V. Kishkina; A. N. Trukhin; S. I. Trukhina (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2025)
In order to study the mechanisms of adaptation to loads that require high endurance, the article analyzes and systematizes the literature and the results of our own studies of the duration of the RRNN interval of the cardiointervalogram/heart rate (HR) in the prone position among athletes, in particular, among cross-country skiers. It has been established that the value of RRNN depends on sports specialization (maximum for athletes training for endurance), on the length of training and the level of sportsmanship (for cross-country skiers, with an increase in the level of skill, the value of RRNN increases, and heart rate decreases), on the periods of the annual cycle. So, the athlete K.D. it is maximum in the preparatory period (1497 ms/40 beats/min), but lower in the competition (1477 ms/40.6 beats/min) and in the transition (1467 ms/ 40.8 beats/min) periods. The value of RRNN also depends on the stage of the training camp, or TCB. So, the athlete K.D. from the beginning of the TS to its end, it gradually increases - from 1423 ms to 1572 ms, and the heart rate decreases accordingly from 42.1 to 38.1 beats/min. It was shown that the type of vegetative regulation of heart activity in elite skiers does not change during the annual cycle (all members of the Tatarstan team had type IV regulation according to the classification of N.I. Shlyk, i.e. vagotonia). This confirms the notion that endurance training increases the influence of the parasympathetic system on the activity of the heart. The results of the study of the elite skier-racer K.D. (the first author of the article), fixing the volume and intensity of the training load in all three periods of the annual cycle, as well as the results of a study of the Tatarstan national team (without fixing the loads), revealed that, in general, throughout the season, including in the preparatory period, the median RRNN correlates with the volume (Vkm; Vmin) training loads (the higher they are, the greater the median RRNN). However, the competitive period is characterized by an inverse dependence of the median RRNN on the volume (Vmin) of the load, which is regarded as a reflection of the formation of an anxiety state in this period, although the formation of an anxiety state in the team of Tatarstan (n = 8) was not detected in the competitive period (they have a median of RRNN in the preparatory period was 1430 ms/42 beats/min), and in the competition period – 1490 ms/40.2 beats/min). The authors conclude that even a palpatory calculation of the heart rate of a cross-country skier in conditions of clinostasis (rest) can serve as a guideline in managing the training process, since an increase in heart rate with exercise therapy indicates a decrease in physical performance, and a progressive decrease in heart rate (up to 38 beats/min) – on its increase, as well as on the formation of the synthesis of non-neuronal acetylcholine (ACh). It is assumed that excessive production of non-neuronal ACh, which can lead to weakness of the sinus node, is prevented by a significant increase in ANS SO activity in elite skiers.